Muscle Relaxation Training with Meditation on Stress Reduction of General Administrative Officer - พฤกษพิทักษ์ สุมนกาญจน์ (Journal of Industrial Business Administration, 2019)
The purpose of this research was to compare the stress of General Administrative Officer before and after muscle relaxation training with meditation. The samples were from General Administrative Officer, who had scores from the stress test higher than P75. Research tools include stress tests, relaxation training, muscle training and meditation. The statistics include average standard deviation parametric inference (paired-samples t-test) results showed that muscle relaxation, meditation, together with the General Administrative Officer makes a lower stress. Statistically significant .05.